Development of Entrepreneurship Education to Shape Entrepreneurial Spirit among Students - Prasakti, Angga Warda; Idrus, Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify the strategies, methods, and impacts of entrepreneurship education in shaping the entrepreneurial character of students. The research approach used is qualitative descriptive with data collection techniques in the form of in-depth interviews, direct observations, and documentation studies. The research subjects consist of students, lecturers, and managers of entrepreneurship programs in universities who have implemented entrepreneurship education. The results show that experiential learning strategies, such as project-based learning, business incubators, and entrepreneurship competitions, are effective in increasing students' interest and entrepreneurial skills.